2019
DOI: 10.1177/0145561319867668
|View full text |Cite
|
Sign up to set email alerts
|

Food-Specific IgE and IgG Antibodies in Patients With Chronic Rhinosinusitis With Nasal Polyps: A Case–Control Study

Abstract: EPOS 2012 states that investigation is needed to study a possible role for food allergy in the initiation and perpetuation of chronic rhinosinusitis with nasal polyps (CRSwNP). Our main goal was to compare serum levels of food-specific immunoglobulin G (IgG) and IgE antibodies in patients with CRSwNP and controls. A prospective case–control study with 33 patients with CRSwNP and 31 controls without CRS was carried out. Clinical data were gathered through a systematic interview and blood sample was collected. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Lill et al found a strong association between CRSwNP and milk allergy, 1397 though neither wheat nor overall incidence of food sensitivity differed between diseased and healthy populations. Other studies comparing systemic IgE for food sensitivity between CRSsNP and CRSwNP demonstrated no such relationship, 1398 with Al‐Quodah finding, “no significant differences in the prevalence, type, number of positive food allergens and class level between the 2 groups.” 1399 These studies present conflicting evidence for the role of food allergy in the pathogenesis of CRSwNP disease (Table X‐5).…”
Section: Chronic Rhinosinusitis With Nasal Polyps (Crswnp)mentioning
confidence: 91%
“…Lill et al found a strong association between CRSwNP and milk allergy, 1397 though neither wheat nor overall incidence of food sensitivity differed between diseased and healthy populations. Other studies comparing systemic IgE for food sensitivity between CRSsNP and CRSwNP demonstrated no such relationship, 1398 with Al‐Quodah finding, “no significant differences in the prevalence, type, number of positive food allergens and class level between the 2 groups.” 1399 These studies present conflicting evidence for the role of food allergy in the pathogenesis of CRSwNP disease (Table X‐5).…”
Section: Chronic Rhinosinusitis With Nasal Polyps (Crswnp)mentioning
confidence: 91%
“…The impact of allergic reactions on the occurrence and development of CRS w NP is still inconclusive 7,8 . Still, available data support that serum IgE is associated with CRS w NP 9–11 . One of the characteristics of the late reaction phase of an allergic reaction is the large number of eosinophilic granulocytes that infiltrate the tissues and act as effector cells 12 .…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Still, available data support that serum IgE is associated with CRS w NP. [9][10][11] One of the characteristics of the late reaction phase of an allergic reaction is the large number of eosinophilic granulocytes that infiltrate the tissues and act as effector cells. 12 Eosinophilic chronic rhinosinusitis (ECRS) is a subgroup of CRSwNP and is associated with severe eosinophilic infiltration and Comprehensive treatment based on surgery is required.…”
Section: Introductionmentioning
confidence: 99%